ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBANGUNAN EKONOMI KABUPATEN PADANG LAWAS UTARA - FITRIANI HARAHAP (Institut Pendidikan Tapanuli Selatan, 2019)
Abstract This study aims to analyze and find out (1) the effect of wages and investment in human resources on labor productivity, (2) the effect of wages, investment in human resources, consumption and labor productivity on the economy. The type of the research is descriptive and associative with data documentary, using simultaneous equation model analysis tools with Indirect Least Squared (ILS) method. The results of the study are: (1) the wages and investment in human resources has influence to labor productivity significantly. It means that, the increase in wages and investment of human resources will increase in labor productivity, and vice versa, if wages and investment in human resources declined will also cause a decrease in labor productivity in North Padang Lawas (2) labor productivity, wages and consumption have a significant effect on the economy. In other words, if there is an increase in labor productivity and consumption while wages decrease will have an impact on improving the economy. Conversely, if there is a decrease in labor productivity and consumption while rising wages will have an impact on the economic downturn, however investment in human resources has no significant effect on the economy in the North Padang Lawas.